Comparison of digital watermarking techniques for the security of voip communications - Er, Füsun Çıtak (My University, 2011)
VOIP HABERLEŞME SİSTEMLERİNİN GÜVENLİĞİ İÇİN DİJİTAL SES DAMGALAMA YÖNTEMLERİNİN KARŞILAŞTIRILMASI Bu tezde, digital ses damgalama teknikleri, oturum başlatma protokolü olarak SIP kullanan gerçek zamanlı iletişim sistemlerinde, kaynak kökenli kimlik doğrulama yöntemi olarak kullanilabileceği sunulmuştur. Önerilen yöntem, iletişim kuran taraflar arasında kaynak köken bilgisi iletimini sağlamak için digital ses damgalama tekniklerini kullanmaktadır. İletişim kuran taraflar, karşılıklı olarak kaynak köken bilgilerini SIP(Oturum Başlatma Protokolü) nün steganographic tekniklerini kullanarak birbirlerine iletirler. Bu çalışmada, digital ses damgalama teknikleri, önerilen yöntemin uygulanabilirliğini göstermek amacı ile gerçek zamanlı çoklu ortam iletişim sistemleri üzerinde uygulandı, gerçek zamanlı çoklu ortam iletişim sistemleri sistemleri sağlamlık, güvenlik, şeffaflık, karmaşıklık, kapasite, doğrulama ve geri alınabilme gibi ölçüt parametreleri açısından değerlendirildi. Deney sonuçları bazı kısıtlar ile birlikte önerilen yönetimin gerçek zamanlı çoklu ortam iletişim sistemlerinde uygulanabilirliğini göstermektedir.

COMPARISON OF DIGITAL AUDIO WATERMARKING TECHNIQUES FOR THE SECURITY OF VOIP COMMUNICATIONS In this thesis, it is presented that digital audio watermarking techniques can be utilized to improve security of Real-Time Communications using Session Initiation Protocol (SIP), such as Voice over IP (VoIP), for source origin authentication. Such watermark-enabled VoIP mechanism utilizes audio watermarking techniques as a covert channel between calling parties to send source origin indicator information during conversation phase of VoIP. In order to exchange source origin indicator information between calling parties, available steganographic techniques for SIP that are used for creating covert channels during signaling phase of VoIP call are evaluated. The effects of audio watermarking were measured using the Signal-to-Noise Ratio, watermark extract durations and the effects of a-law encoding during transportation phase of VoIP. Moreover, various audio watermarking algorithms were implemented to demonstrate applicability of defined security solution in terms of certain parameters, like: robustness, evaluation times, complexity and capacity. The Experimental results showed that some watermarking algorithms are applicable in VoIP while some are not suitable for source origin authentication.
Keywords: Bilgisayar Mühendisliği; Haberleşme Sistemleri